2017
DOI: 10.1016/j.otsr.2017.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the surgical management of odontoid fractures in patients above 75 years of age: Retrospective study of 70 cases

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 28 publications
0
16
0
2
Order By: Relevance
“…Fractures at the odontoid base, classified as Type II injuries by Anderson and D'Alonzo system, are the most common type (more than 60%) of all odontoid fractures [8,11,14,15]. They were considered relatively unstable and had a high incidence of nonunion [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fractures at the odontoid base, classified as Type II injuries by Anderson and D'Alonzo system, are the most common type (more than 60%) of all odontoid fractures [8,11,14,15]. They were considered relatively unstable and had a high incidence of nonunion [5].…”
Section: Discussionmentioning
confidence: 99%
“…Conservative treatment for this type is associated with high bony nonunion rate, accordingly, surgical treatment is recommended [1,5]. Over the past few decades, the applications of several surgical strategies (odontoid screw fixation, Magerl technique, and Harms technique) have achieved satisfying clinical results [3,[9][10][11][12][13]. It was reported that posterior approaches can achieve high bone union rate [14,15], but they inevitably sacrificed atlantoaxial rotational motion [5,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Dagegen werden unter chirurgischer Therapie knöcherne Heilungsraten von bis zu 100 % angegeben [28]. Auch Metaanalysen zeigen eine signifikant höhere Knochenbruchheilung bei den operativ versorgten Patienten [26].…”
Section: Behandlungunclassified
“…This technique was pioneered by Goel et al 9 and modified by Harms and Melcher. 10 It was recently promoted by Faure et al 6 but they did admit that it was demanding and that the main technical challenge was related to bleeding of the venous plexus around the C2 nerve root and at the screw entry points on the C1 lateral masses. Huang et al 8 also expressed concerns regarding the risk of blood loss during exposure of the C1 lateral masses and noted the additional intraoperative risks of vertebral artery injury and nerve dysfunction after dissection of the C2 nerve root.…”
Section: Introductionmentioning
confidence: 99%